2022
DOI: 10.1111/1750-3841.16333
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of gluten‐free rice flour bread through the addition of high‐temperature water during processing

Abstract: Recently, there has been an increase in the demand for gluten-free bread due to health reasons. One of the flours used to produce gluten-free bread is rice flour; flour characteristics are very important for breadmaking. Although a study has shown that the addition of high-temperature water can improve the quality of rice flour bread, studies are yet to consider different rice properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…Essa farinha é considerada um produto versátil, pois possui sabor suave, propriedades hipoalergênicas, níveis baixos de sódio e carboidratos de fácil digestão. Sendo uma das mais indicadas para o desenvolvimento de produtos de panificação isentos de glúten (Cappelli et al, 2020;Saito et al, 2022).…”
Section: Farinha De Arrozunclassified
See 1 more Smart Citation
“…Essa farinha é considerada um produto versátil, pois possui sabor suave, propriedades hipoalergênicas, níveis baixos de sódio e carboidratos de fácil digestão. Sendo uma das mais indicadas para o desenvolvimento de produtos de panificação isentos de glúten (Cappelli et al, 2020;Saito et al, 2022).…”
Section: Farinha De Arrozunclassified
“…Estudos demonstram que para se obter melhores atributos tecnológicos e sensoriais em pães elaborados com farinha de arroz, alguns ingredientes são adicionados tais como: amido modificado, hidrocoloides, probióticos e outras fontes de proteínas e enzimas, como α -amilase, transglutaminase, glicose oxidase, lipase, proteases, amilases e tirosinase, que atuam como auxiliares para o desenvolvimento e fortalecimento da massa sem glúten (Palabiyik et al, 2016;Pongjaruvat et al, 2014;Honda et al 2021;Sarabhai et al, 2021). Saito et al (2022) investigaram o efeito da adição de água em alta temperatura nas características da farinha de arroz e na qualidade do pão. Observaram que, independentemente das características do arroz, tais como: teores de amilose (12,1% a 24,5%), amido danificados (2,4% a 5,5%), granulometria média (16,3 a 63,3 µm), proteínas (5,4% a 6,1%) e umidade (12,0% a 15,0%), os pães elaborados com adição de água quente, entorno de 70ºC apresentaram características tecnológicas adequadas, como maior do miolo dos pães, em comparação as formulações elaboradas com adição de água fria (5°C).…”
Section: Farinha De Arrozunclassified
“…However, few works such as Torbica et al (2019), Comettant-Rabanal et al (2021), Saito et al (2022a), Saito et al (2022b and Saito et al (2022c) have used 100% whole grains flours (corn, oat, millets, sorghum, rice, and rye) pre-treated by heated water and/or extrusion cooking to produce fibre-rich GF breads with volume, instrumental texture, and the sensory characteristics similar to counterparts obtained with partial replacement of extruded flour. The latter usually requires the addition of hydrocolloids, proteins, and other functional ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that regardless of the characteristics of the rice, bread made with the addition of warm water was fluffier and softer than bread made with cold water (5°C). The optimal water temperature and the degree of starch gelatinization increased for the variety of ror rice flour with a lower amylose content in case of the similar particle size [8]. In addition, in food production technologies, the use of activated water is becoming widespread to increase their efficiency [9].…”
Section: Introductionmentioning
confidence: 99%